Identification and genetic analysis of candidate genes for resistance against Phytophthora sojae in soybean using a genome-wide association study - Park, Hye Rang; Heo, Su Vin; Kang, Beom Kyu; Seo, Hyoseob; Lee, Eunsoo; Park, Jihee; Jang, Yun Woo; Seo, Jeong Hyun; Park, Girim; Kim, Jun Hoi; Lee, Yeong Hoon; Han, Won Young; et al. (Frontiers in Plant Science, 2025)
Phytophthora root and stem rot (PRSR), an infection caused by Phytophthora sojae in soybean [Glycine max (L.) Merr.], is an important threat to soybean production in South Korea; however, the precise genetic mechanisms related to PRSR resistance remain largely unclear, limiting the development of resistant cultivars. This study aimed to identify candidate resistance (R) genes related to PRSR resistance in soybeans through a genome-wide association study (GWAS). We evaluated 205 soybean accessions inoculated with P. sojae isolates GJ3053 or AD3617 using the hypocotyl inoculation method and genotyped them using a 180K Axiom SoyaSNP chip. We identified 19 significant single-nucleotide polymorphisms (SNPs) related to resistance against one or both of the two isolates: GJ3053 resistance was associated with SNPs on chromosomes 2, 3, 9, 10, 14, and 16, whereas AD3617 resistance was related to SNPs on chromosomes 3, 13, and 16. The SNP AX-90410433 (3,628,549 bp) on chromosome 3 was significantly linked to resistance against both isolates, based on the linkage disequilibrium (480 kb) and –log10(p) values (6.62). This region harbors key resistance gene analogs (RGAs), including nucleotide-binding site leucine-rich repeat and serine-threonine protein kinases. Among the 34 identified RGAs in the 2.9–4.4 Mbp region, Glyma.03g036500, which encodes a protein with serine kinase activity, emerged as a strong candidate. Haplotype analysis revealed that this gene exhibited genotypic patterns consistent with the resistance phenotypes of the selected accessions. Validation through gene expression and kompetitive allele-specific PCR marker analysis supported the role of Glyma.03g036500 in PRSR resistance. These findings underscore the significance of identifying and utilizing PRSR resistance genes, such as Glyma.03g036500, to enhance pathogen resistance in soybean breeding programs. Our results can inform the development of cultivars with improved resistance to P. sojae, thus potentially mitigating the effect of pathogenic stress on crop productivity and quality, and contributing to sustainable agriculture.